Condo hotels as a way to invest in new market challenges - Stoch-Chyc, Halina (Hotele condo jako sposób na inwestycję w aspekcie nowych wyzwań rynkowych, 2019)
The Polish hotel market has been witnessing a continuous growth in the supply of condo facilities. Thanks to them, areas where investments are located benefit from them (infrastructure development takes place, region attractiveness increases, the city’s budget is augmented by taxes) and also individual entrepreneurs investing in the purchase of premises. The aim of this paper is to identify the values generated by investments in condo hotels in Poland. The analysis covered selected facilities whose profit proposals were compared with the level of interest rates. The practical part, determining the costs and benefits of owning a condo apartment, was preceded by theoretical considerations on investment. The whole issue has been determined within the scope of behavioral economics which has a dominant influence on purchasing decisions. The paper is a result of the analysis of available literature sources, primary data obtained from condo operators and secondary data on investment issues
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 185-199
Keywords: investments; condo hotel; real estate; inwestycje; condo hotele; nieruchomości